ANALISIS AESO POLYMER COATING PADA SERAT WARU TERHADAP SIFAT MEKANIK, PENYERAPAN AIR DAN MORPHOLOGY KOMPOSIT POLYESTER - Suteja; Herlina Sari; Syarif Hidayatullah (POLITALA PRESS, 2025)
In this study, a method of improving the performance of Waru fiber reinforcement composites by NaOH and AESO coating treatment is reported. Waru fiber (WF) as composite filler was varied raw WF (WR), NaOH treated WF (WH) and NaOH+AESO coating treated WF (WHC) and tested for mechanical characteristics, water absorption, and morphology of the composites. The results showed that the bending and tensile strength increased the highest by 27.65% and 58.66% respectively for WHC composites. AESO coating treatment decreased the elongation percentage of the composite but increased the elastic modulus of the composite. The SEM photo morphology of the composites showed fiber clumping, fiber pull out, and trapped voids. NaOH-treated WF showed better interface bonding with the polyester matrix. For the AESO coating treatment, the WF-polyester matrix surface interaction was observed with hackles appearing on the composite fracture surface.